Dissemination of the Importance of Numbering Medical Records at the Parak Karakah Padang Health Center - Nila Mayasari; Nurhasanah Nasution (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Puskesmas is a health service facility that organizes community health efforts and first level individual health efforts. The medical record is a record or record of who, what, why, when and how services are provided to patients during the treatment period. The family folder is a record of health conditions. Family folder is a record of health conditions, as a result of health problems or diseases that are stored in one medical record document folder. The medical record storage system is one of the most important factors in health care institutions. Because the storage system can facilitate medical record files stored in storage racks, speed up retrieval or retrieval of stored medical record files Purpose of numbering medical records Facilitate search of medical record files or documents when patients then come back for treatment at health care facilities as well as for continuity information, by using a numbering system, the information can be sequential and minimize lost information.